Sensorless method of controlling the position of the movable element of the electric machine of the reciprocating action of - R. R. Gibadullin; A. N. Tsvetkov; I. V. Ivshin; L. V. Dolomanyuk (Известия высших учебных заведений: Проблемы энергетики)
The article describes a Sensorless method for determining the position of the movable element electrical machines reciprocating action. The method is implemented on the basis of the data voltages of the windings and the results of measurements of parameters of electrical machines reciprocating action.